An analysis of the wake of pedalling cyclists in a tandem formation - Barry, N.; Burton, D.; Sheridan, J.; Thompson, M.; Brown, N. A. T. (Procedia Engineering, 2016)
Aerodynamics is a critical factor in the performance of cyclists, with drag being the dominant resistive force at racing speeds. Many cycling events involve athletes riding in close proximity. Previous studies have shown that flow interactions result in significant drag reductions for tandem cyclists, inline parallel to the flow. However, the flow mechanisms associated with these changes have not been well characterised to date.